Islamic Philanthropy Empowerment Fund in Social Economic Affairs - Hanan Sabila; Endah Saptutyningsih (Universitas Muhammadiyah Yogyakarta, 2020)
The development of Islamic Philanthropy funds raises many questions about its use, especially the use directed at productive use. Zakat management authorities, including LAZISMU, began to develop the use of philanthropic funds in the socio-economic sector for the Empowerment Programme. Based on the level of operation of these funds for successful programs, the Yogyakarta Regional Leaders are classified as the most developed, mainly in the Sleman Regency area. There will be many findings in this study regarding Mustahik and Amil's views on the economic empowerment system implemented by LAZISMU Regional Leader of Muhammadiyah (Pimpinan Daerah Muhammadiyah) Sleman, beginning with Empowerment Indicators, Changes in Mustahik Economic Conditions and Utilization Effectiveness using statistical methods as instruments explain the results. In this study, most of these things show significant results based on the Mustahik's point of view.